Idiopathic palmoplantar hidradenitis: report of 2 cases - Alonzo Caldarelli, Agostina B.; Granillo Fernández, Sofía; Moreno, María V.; Maier, Patricio; Taboada, Marcia A. (Revista del Hospital Italiano de Buenos Aires, 2024)
Idiopathic palmoplantar hidradenitis is a rare neutrophilic dermatosis that manifests as painful erythematous papules, plaques or erythematous edematous nodules on the soles and/or palms of healthy pediatric patients. We consider it important to recognize it as a benign, self-resolving disorder with multiple differential diagnoses.